Kham space & the act of space - Ray, Bappa; Indira Gandhi National Centre for the Arts. (New Delhi : Indira Gandhi National Centre for the Arts, 2013)
The film is documentation of an exhibition organized in 1986 called "Kham". The documentary highlights the five elements and looks at space as a concept within which life style delves. It shows how the world is surrounded by the cosmic water. Again it talks about the root of the universe and the universe being the body of the cosmic man and Kham is the space where it sustains. It looks at civilization on timeline and fathoms the architecture to look at the space within its dynamic meaning and show how space travel through time within the spectrum of creativity. The film is an enquiry to understand the world views of space through images. Thus in short the film showcases how Kham as space remained cosmic manifestation where from idea of life, life style got encoded in various symbols.
Copyright notice on container: Indira Gandhi National Centre for the Arts, New Delhi.
Summary taken from container.
Editor, Pria Devi, Madhavan Palat ; music Christine Sathiah, Satish Gupta, Pria Devi, Indrani Rahman.
Keywords: Cosmology; Space and time; Documentary films; Nonfiction films